A reference high-pressure CH4 adsorption isotherm for zeolite Y: results of an interlaboratory study - Nguyen, H. G.T.; Sims, C. M.; Toman, B.; Horn, J.; van Zee, R. D.; Thommes, Matthias; Ahmad, R.; Denayer, J. F.M.; Baron, G. V.; Napolitano, E.; Bielewski, M.; Mangano, E.; et al. (Adsorption-Journal of the International Adsorption Society, 2020)
This paper reports the results of an international interlaboratory study led by the National Institute of Standards and Technology (NIST) on the measurement of high-pressure surface excess methane adsorption isotherms on NIST Reference Material RM 8850 (Zeolite Y), at 25 °C up to 7.5 MPa. Twenty laboratories participated in the study and contributed over one-hundred adsorption isotherms of methane on Zeolite Y. From these data, an empirical reference equation was determined, along with a 95% uncertainty interval (Uk=2). By requiring participants to replicate a high-pressure reference isotherm for carbon dioxide adsorption on NIST Reference Material RM 8852 (ZSM-5), this interlaboratory study also demonstrated the usefulness of reference isotherms in evaluating the performance of high-pressure adsorption experiments.
CRIS-Team Scopus Importer:2020-09-18
Keywords: CH; CO; High-pressure adsorption isotherm; Interlaboratory study; Reference isotherm; Reference material; RM 8850; RM 8852; Surface excess adsorption; Zeolite Y; ZSM-5